Tracking The Efficiency Of Cholesterol Bioconversion By Nocardia Sp. Mtcc 1534 In Presence Of Some Ring Cleavage Inhibitors By Gas Chromatography - JANKI G. VYAS,; KIRTI S. PAWAR,; JAY K. JETHVA,; JINAL H. SHAH, (International Journal of Pharma and Bio Sciences, 2012)
Nocardia sp. MTCC 1534 was found to utilize cholesterol as sole source of carbon and energy. Growing culture of the organism was incubated with reported 9-alpha-hydroxylase inhibitors for accumulation of 17-ketosteroids. The inhibitors used in the present investigations were isopropanol, cupric chloride and 8-hydroxy quinoline. The effect of concentration and time of addition of inhibitors was studied and products accumulated were analysed with the help of thin layer chromatography. The dried extracts of bioconversion medium in organic solvents were subjected to Gas chromatography and peaks of bioconversion products analysed by Mass spectroscopy. In case of Nocardia sp. MTCC 1534 it was observed that all 3 inhibitors i.e. cupric chloride, 8-OH-quinoline and isopropanol give maximum variety of products at 48 hrs of incubation periods which decline afterwards. Hence, 48 hr incubation was recommended time period after growth of organisms and substrate addition for accumulation of products which were proposed to be 17-ketosteroids on the basis of mass analysis.